Pusat Seni Dan Kebudayaan Di Kuantan Singingi Dengan Pendekatan Arsitektur Tradisional (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Every district in Riau province has an arts and culture diverse, as well as the Kuantan Singingi regency. Arts and culture in Kuantan Singingi are still implemented and growing routinely in community life. that is the reason of art and culture center is needed. Arts and Culture Center in Kuantan Singingi is an area that aims to facilitate the activities of arts and culture in Kuantan Singingi regency.Traditional Architecture of Kuantan Singingi be applied to the design, then is found the Tungku Tigo Sajorangan concept, which means the three customary elements are interrelated, to be applied in the design. Method of design Arts and Culture Center in Kuantan Singingi designed by transforming traditional architecture of Kuantan Singingi, namely the Rumah Godang Koto, Balai Adat Koto and Mesjid Koto. The elements of design in traditional Architecture includes regional of patterns and shape of the building mass be transformed in accordance with the state of region and traditional buildings in the Koto area. From the process of traditional building transformation, so that can create a region of Art and Culture Center in Kuantan Singingi with Traditional Architecture.Keywords: Kuantan Singingi, Art and Culture Center, Traditional Architecture, Design Transformation.